Formulasi Sediaan Hand Body Lotion Menggunakan Ekstrak Etanol Daging Buah Kedondong (Spondias dulcis Soland. ex Forst. fil.) Sebagai Pelembab Kulit - Sudewi Sudewi; Yessi Febriani; Siti Raudah; Ira Nofriani; Nilsya Febrika Zebua (Journal of Pharmaceutical and Health Research, 2021)
Kedondong fruit (Spondias dulcis Soland. Ex Forst. Fil.) Is a fruit plant originating from South and Southeast Asia and spread in tropical areas. Kedondong fruit contains vitamins A, B and C, carbohydrates, protein and fat. This study aims to determine the pulp of kedondong (Spondias dulcis Soland. Ex Forst. Fil.) In the form of ethanol extract which can be formulated into a hand body lotion which at certain concentrations can provide a moisturizing effect on the skin and is not irritating. This research was conducted using experimental methods, using the test material of the pulp of the kedondong fruit (Spondias dulcis Soland. Ex Forst. Fil.). The ethanol extract of kedondong pulp (Spondias dulcis Soland. Ex Forst. Fil.) Was obtained by maceration using 96% ethanol filter, then concentrated using a rotary evaporator. The preparation is formulated into a hand body lotion with a concentration of 0.5%, 1.5%, 2.5% and 3.5%, as well as a blank. Examination of the physical quality of the preparation includes, homogeneity test, pH test, emulsion type test, stability test, irritation test and effectiveness test of the preparation in moisturizing the skin and comparing with preparations on the market using the Skin Moisturer Checker (AramÒ) and statistical data processing was carried out using the SPSS 26.00 ANOVA method. The results showed that the pulp of kedondong (Spondias dulcis Soland. Ex Forst. Fil.) In the form of ethanol extract can be formulated into a hand body lotion, a homogeneous preparation with the type of oil-in-water emulsion (M / A), has a momentary pH range. After making 6,6-7,3 and pH after 12 weeks of storage 6,3-7,0, the effectiveness test of moisture preparation at a concentration of 3.5% (Formula E) gave moisture (32%) categorized as "moist" which was statistically showed a significant difference with the comparison results, the hand body lotion that was made did not irritate the skin.